Standard handbook of plant Engineering - Rosaler, Robert C. (McGraw-Hill, 2002)
In the Standard Handbook of Plant Engineering, Second Edition, Robert C. Rosaler and 70 other industry experts take you on an exhaustive tour of the basic plant facility, plant operation equipment and the all-important maintenance function-giving you the hands-on skill and essential technical data you need to keep your plant running smoothly. You get complete, up-to-the-minute details on: In-plant prime power generation and cogeneration; Heating, ventilating and air conditioning; Water sources, use and disposition; Mechanical power transmission; Instrumentation and automatic control; Pollution control and waste disposal; Plant safety and sanitation; Energy conservation; Lubricants and lubrication systems.